A comparative follow up study of transabdominal preperitoneal mesh repair in inguinal hernias with or without mesh fixation - Sajida Qureshi; Ghazanfar, Shahriyar; Aftab Ahmed Leghari; Muhammad Zubair; Sadaf Chisti; Fahad Memon; Mohammad Saeed Quraishy (Journal of the Pakistan Medical Association, 2020)
A comparative follow up study of transabdominal preperitoneal mesh repair in inguinal hernias with or without mesh fixation